Marginalization of health institute professional groups: societal approach - Krom I.L.; Yerugina M.V.; Kovalev Ye.P.; Yeremina M.G.; Vlasova M.V.; Dolgova E.M.; Bochkareva G.N. (Саратовский научно-медицинский журнал, 2017)
The process of institutionalization of healthcare, which is considered as one of the basic social institutions, is realized in qualitative changes in its structure. The authors note that changes in the social structure, the social differentiation increasing, crisis and dysfunctional processes in the healthcare institution in modern Russia have led to a change in status, social mobility descending and marginalization of the social and professional groups of the healthcare institute. In the authors' opinion the process of marginalization of the social and professional groups of the healthcare institute is explained by the «concept of status inconsistency» proposed by G. Lensky.